ANALISIS KETERKAITAN ANTAR SEKTOR DI PROVINSI ACEH - Maulana, Riski; Jamal, Abd (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study aims to analysis which sector the most superior in the province of Aceh. This study uses secondary data processing methods. 9 sectors selected for analysis consisted of Agriculture, Mining and Quarrying Manufacturing Electricity, Gas and Water, Construction, trading, Hotels and Restaurants, Transport and Communication, Finance, Leasing and Business Services and Services. Through his analysis using input-output analysis can be ascertained which sectors are the most crucial as follows: Industrial Products pengilingan Oil and Gas, Land Transport and Industrial Goods sector of Metal, Machinery and Equipment becomes Sector base in the province. Expected for the Aceh government to be able to create policies that can encourage the growth of a sector basis in addition to empowering potential of this sector in terms of supporting the non base. These efforts must be supplied by the government of Aceh in order to provide benefits to the people of Aceh.Keywords: Total Sectors, Economic Growth, Input-Output.